2012
DOI: 10.1371/journal.pone.0042609
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening and Rapid Inhibitor Triage Using an Infectious Chimeric Hepatitis C Virus

Abstract: The recent development of a Hepatitis C virus (HCV) infectious virus cell culture model system has facilitated the development of whole-virus screening assays which can be used to interrogate the entire virus life cycle. Here, we describe the development of an HCV growth assay capable of identifying inhibitors against all stages of the virus life cycle with assay throughput suitable for rapid screening of large-scale chemical libraries. Novel features include, 1) the use of an efficiently-spreading, full-lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Recently, several groups have reported cell-based HCV infection systems for the screening of HCV inhibitors in various assay formats (12)(13)(14)(15). Traditionally, HTS was performed at a single fixed concentration of each candidate compound, which is prone to false positives and false negatives and requires extensive follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several groups have reported cell-based HCV infection systems for the screening of HCV inhibitors in various assay formats (12)(13)(14)(15). Traditionally, HTS was performed at a single fixed concentration of each candidate compound, which is prone to false positives and false negatives and requires extensive follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated that reporter genes can be genetically engineered into certain locations of the HCV genome without impairing the viability of the virus (11). Several groups have reported cell-based HCV infection systems for the screening of HCV inhibitors in various assay formats (12)(13)(14)(15). Gastaminza et al developed a colorimetric assay measuring HCV E2 protein produced by HCVinfected cells in a 96-well plate format (12).…”
Section: H Epatitis C Virus (Hcv) Infection Affects Approximately 200mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant deterrent to automated anti-RABV drug discovery, for instance, is the BSL2/3 containment requirements imposed by replication-competent RABVs and mandatory rabies vaccination as well restriction to the laboratory of not vaccinated people.. Based on the original reverse genetics system developed for the SAD-B19 RABV strain [64], however, minireplicon systems and single-cycle reporter RABV viruses were developed that allow study of the RABV polymerase activity and in-cell replication in a BSL2 setting [65][66][67][68][69][70][71][72][73]. Analogous to the precedent set by successful screens employing single-cycle HIV, hepatitis C virus, and influenza virus reporter strains [74][75][76], the single-cycle based approach in particular offers an exciting drug discovery perspective. Transient-transfection based minigenome drug screens have furthermore been attempted to identify, for instance, Ebola virus polymerase inhibitors [77][78][79].…”
Section: Anti-rabv Drug Discoverymentioning
confidence: 99%
“…Reporter genes inserted into certain locations of the HCV genome could yield viable HCV capable of infection and replication in the cell culture (Koutsoudakis et al, 2006). In recent years, several groups have applied either wild-type HCV or modified HCV with reporter genes to develop cell-based HCV infection systems for the screening of HCV inhibitors (Chockalingam et al, 2010; Gastaminza et al, 2010; Kim et al, 2007; Wichroski et al, 2012; Yu et al, 2012). Cell-based HCV infection systems have the advantage of targeting various stages of HCV life cycle, thus significantly improving the efficiency of the drug screening process.…”
Section: Introductionmentioning
confidence: 99%